2016
DOI: 10.1111/cpr.12236
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of CD61 promotes hUC‐MSC differentiation into male germ‐like cells

Abstract: Under induction of BMP4, CD61-overexpressing hUC-MSCs, which had turned into PGC-like cells, could be further differentiated into male germ-like cells. Thus, a simple and efficient approach to study male germ cell development by using hUC-MSCs has been established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…PGC-like cells, which are positive for SSEA1 and CD61, can develop into spermatid cells19. Our previous studies showed that CD61 promotes hUC-MSCs to differentiate into male germ-like cells12. Nevertheless, the mechanism of CD61 in PGC development remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PGC-like cells, which are positive for SSEA1 and CD61, can develop into spermatid cells19. Our previous studies showed that CD61 promotes hUC-MSCs to differentiate into male germ-like cells12. Nevertheless, the mechanism of CD61 in PGC development remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that MSCs derived from bone marrow and umbilical cord can differentiate into germ-like cells1011. Our previous investigation also demonstrated that human umbilical cord mesenchymal stem cells (hUC-MSCs) can potentially differentiate into germ-like cells under treatment with CD61 and bone morphogenetic protein 4 (BMP4)12. However, the mechanisms remain unclear.…”
mentioning
confidence: 99%
“…Molecular evaluation on day 7 post-treatment with BMP4 revealed that the expression of some GC-specific markers like SSEA-1, Prdm1, Prdm14, Ap2c, Stella, Sox2, C-kit, Stra8, Scp3 and Prm1 were upregulated in the transfected cells far more than in the non-transfected BMP4 treated human UC-MSCs. Although the researchers claimed that they saw a number of spermatid-like cells, which expressed post meiotic marker, Acr, they did not show further evidence such as the chromosomal content and fertilizing capacity of the cells [44].…”
Section: Umbilical Cord (Uc)-mscsmentioning
confidence: 97%
“…Fang et al . and Li et al proved that CD61 could promote the differentiation of ADMSC into PGC-like cells through activation of the TGF-β pathway ( Li et al, 2016 ; Fang et al, 2017 ). Wei et al .…”
Section: The Mechanism Of Treating Pof With Mscsmentioning
confidence: 99%